Answer:
2.7 in²
Step-by-step explanation:
similar triangles have the same angles, and all side lengths (or other distances) of one triangle have the same scaling factor to the side lengths of the other triangle.
so, we know the relation between the 2 baselines is 2/3, as this is the factor to turn the baseline of the large triangle into the baseline of the smaller triangle.
in other words
EF = BC × 2/3
2 = 3 × 2/3
correct
how do we calculate the area of a triangle ?
Area = baseline × height / 2
from BAC we know
Area = 6
baseline = 3
height = ?
6 = 3 × height / 2
12 = 3 × height
height = 4
aha !
now, EDF has a height too that we need to calculate is Area. and this height has the same scaling factor compared to the larger triangle as the side lengths : 2/3
so, for EDF we know
Area = ?
baseline = 2
height = 4 × 2/3 = 8/3
therefore, the area is
Area = (2 × 8/3) / 2 = (16/3) / 2 = 8/3 = 2.66666... ≈ 2.7
the shirt answer would be :
we know from the 2 baselines that the scaling factor for each distance is 2/3.
for the area we need to multiply 2 distances, so that means we have to multiply both by 2/3. and so on the formula for the area we have to use 2/3 × 2/3.
2/3 × 2/3 = 4/9
=>
Area small = Area large × 4/9 = 6 × 4/9 = 24/9 = 8/3 ≈ 2.7
Answer:He should buy the six pack.
Step-by-step explanation:
The total number of hotdogs that the shopper needs is 48.
The store sells identical hot dogs in 2 differently sized packages. They sell a six pack hot dog for $2.10, and an eight pack of hot dog for $3.12.
If the shopper buys the six pack hot dog, he would need to buy 8 of it. The total cost would be
8 × 2.10 = $16.8
If the shopper buys the eight pack hot dog, he would need to buy 6 of it. The total cost would be
6 × 3.12 = $18.72
The 6 pack is cheaper than the eight pack. Therefore,
He should buy the six pack.
point slope equation formula: y - y1 = m (x - x1)
(-1,4) (-2,1)
answer:
1 -4 = 3 (-2+1)
Answer:
Step-by-step explanation:
The population in 2003= 47000
Since the population increase by 1200 every year,
in 2004 the population will be 47000+1200
in 2005 the population will be 47000+(1200+1200) which is the same as
47000+2(1200) where 2 is 2 years after 2003,
Therefore the population x years after 2003 is 47000+x(1200).
P= 47000+1200x
b) The population at 2009 which is 6 years after 2003 will be
47000+(1200)*6=47000+7200= 54200
The population at 2009 is 54200,
Answer:
idk a or c
Step-by-step explanation: